Multisensory Method Training in Craft Arts (Fabric Marbling) for Students with Hearing Impairments (Lembaga Pengembangan Kinerja Dosen, 2026)
Students with deaf disabilities often have difficulty understanding verbal instruction, but have significant advantages in visual and motor aspects. This service activity aims to apply multisensory methods through Suminagashi craft art training (cloth marbling) to improve students' fine motor skills and creativity at SLB B Yakut Purwokerto. The implementation method uses a descriptive qualitative approach with a